Handbook of Psychological Assessment, Case Conceptualization, and Treatment Vol.2 - Hersen, Michel and Rosqvist, Johan; Edited By Reitman, David (Hoboken Wiley, 2008)
Handbook of Psychological Assessment, Case Conceptualization, and Treatment provides in two volumes comprehensive coverage of the fundamentals of psychological practice across the age spectrum and
Include Index
Keywords: Psychology, Pathological